Fibroblast growth factor–transforming growth factor beta dialogues, endothelial cell to mesenchymal transition, and atherosclerosis. Issue 5 (October 2018) - Chen, Pei-Yu; Simons, Michael
Abstract : Purpose of review: Despite much effort, atherosclerosis remains an important public health problem, leading to substantial morbidity and mortality worldwide. The purpose of this review is to provide an understanding of the role of endothelial cell fate change in atherosclerosis process. Recent findings: Recent studies indicate that a process known as endothelial-to-mesenchymal transition (EndMT) may play an important role in atherosclerosis development. Transforming growth factor beta (TGFβ) has been shown to be an important driver of the endothelial cell phenotype transition. Summary: The current review deals with the current state of knowledge regarding EndMT's role in atherosclerosis and its regulation by fibroblast growth factor (FGF)–TGFβ cross-talk. A better understanding of FGF–TGFβ signaling in the regulation of endothelial cell phenotypes is key to the development of novel therapeutic agents.